2023
DOI: 10.1177/15553434231156417
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Approach to Examining Team Coordination Breakdowns During Crisis Situations

Abstract: During crisis situations, teams are more prone to coordination breakdowns that are characterized by a temporary, diminished ability to function effectively as a team. However, team research currently lacks robust approaches for identifying transitions from effective team functioning to coordination breakdowns. With the current study, we aimed to develop such robust approaches, and to deepen our understanding of how team coordination dynamics across various physiological signals reflect coordination breakdowns.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 86 publications
1
7
0
Order By: Relevance
“…The current study is a secondary analysis of an existing dataset 10 . An extensive description of this data, including details less relevant to this study, can be found on the Open Science Framework (OSF; https://osf.io/t9eym).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The current study is a secondary analysis of an existing dataset 10 . An extensive description of this data, including details less relevant to this study, can be found on the Open Science Framework (OSF; https://osf.io/t9eym).…”
Section: Methodsmentioning
confidence: 99%
“…Three raters identi ed the TCBs in the audiovisual recordings of participants combined with the game recordings 10 . Interrater reliability was found to be good (Cohen's Kappa = .67.…”
Section: Manually and Computationally Identifying Tcbsmentioning
confidence: 99%
See 3 more Smart Citations